2006
DOI: 10.1080/00015458.2006.11679913
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life after Hip Fracture Surgery in the Elderly

Abstract: As the world population ages, the prevalence of osteoporosis and the incidence of hip fractures will increase dramatically, being responsible for an increase of the health expenditure. On the other hand, there is the inescapable fact of scarcity creating the necessity of making difficult choices with regard to the allocation of human resources. So the question remains: should we carry on investing an important part of our health expenditure for the treatment of hip fractures in elderly people? To answer this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
1
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 19 publications
0
21
1
6
Order By: Relevance
“…1 Approximately 30% of patients under the age of 80 years were unable to walk independently 1 year after hip fracture and became home-bound; 20% to 40% of patients were admitted to an elderly care home; and all patients suffered both physically and psychologically with re-fracture and fear of falls. 2 Hip fracture patients with poor functional recovery are unable to resume their prefracture function with a consequent deterioration in quality of life. Mortality at 1 year after hip fracture was as high as 27% in males and 15% in females.…”
Section: Introductionmentioning
confidence: 99%
“…1 Approximately 30% of patients under the age of 80 years were unable to walk independently 1 year after hip fracture and became home-bound; 20% to 40% of patients were admitted to an elderly care home; and all patients suffered both physically and psychologically with re-fracture and fear of falls. 2 Hip fracture patients with poor functional recovery are unable to resume their prefracture function with a consequent deterioration in quality of life. Mortality at 1 year after hip fracture was as high as 27% in males and 15% in females.…”
Section: Introductionmentioning
confidence: 99%
“…Через 1 год после перелома летальность, по данным ли-тературы, варьирует в очень широком диапазоне от 14,85 до 48,5%, хотя в большинстве работ показатель составляет 21 -34% [10, 15,16,17,18,19,20,21,22,23,24,34]. В про-веденном исследовании летальность через год составила 29,82%, то есть была сопоставима.…”
Section: Discussionunclassified
“…В про-веденном исследовании летальность через год составила 29,82%, то есть была сопоставима. Хотя при этом следу-ет отметить, что во многих работах приводятся данные по показателю летальности только среди прооперированных пациентов, что, в свою очередь, составляет от 21,2 до 30% [17,15,16,19,20]. В г. Ярославле через 1 год наблюдения изучаемый показатель оказался равным 24,76%.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Thus, elderly people are much more subject to complications, both during the immediate postoperative period and later on (8) . Studies in developed countries have suggested that certain preoperative factors are associated with higher mortality rates among patients presenting hip fractures on admission, for example: nonwhite color (3,(9)(10)(11)(12) , advanced age (11,(13)(14)(15) , presence of dementia (16)(17)(18) , male sex (13,19,20) , clinical comorbidities (11,14,16,21,22) and delirium (18,23,24) . In view of the importance that fractures of the proximal femur have for society, our aim was to determine the mortality rate and preoperative factors related …”
Section: Introductionmentioning
confidence: 99%